Hand, foot, and mouth disease in adults caused by Coxsackievirus B1-B6 - Anama Di Prinzio; Dolores Pilar Bastard; Ana Clara Torre; Luis Daniel Mazzuoccolo (Sociedade Brasileira de Dermatologia, 2022)
Abstract Hand, foot, and mouth disease is a viral rickettsial disease caused by Coxsackievirus A16 and Enterovirus 71 in most cases. It is commonly seen in children under ten years old, who present oral enanthema and a macular, maculopapular, or vesicular rash on their hands and feet. However, an increase in cases caused by other viral serotypes was observed in adults in recent years with various clinical presentations and a troublesome diagnosis. Three cases of hand, foot, and mouth disease are reported to show the clinical variability and diagnostic complexity that this disease may present in adult patients.